Impacto de las políticas en ciencia, tecnología e innovación tecnológica propuestas por CONCYTEC, en el marco de la Ley Universitaria 30220, en las universidades peruanas - Diaz Romero, Virginia Elizabeth (2022)
The objective of this thesis is to analyze the impact of public policies related to Science, Technology, and Technological Innovation (STI) proposed by Concytec, on Peruvian universities within the framework of University Law 30220. Using a qualitative methodology, the analysis was made on human resources and scientific production as indicators, for the years 2018 and 2020. In this way, data obtained from the reports made by Sunedu and Concytec are analyzed, allowing the comparison, and understanding of the advances and challenges of Peruvian universities in the current studied context. The results of this research show that the impact of STI policies has given optimistic results based on the evolution of the evaluated indicators. However, the progress made by universities is still limited if we compare it with other countries in the region. This is due to the low investment, the poor continuity of the policies implemented, and the poor interest on the part of the governments in power.